Changing urban mosques in the city: the role of communal and intercultural spaces in Malaysia - Nizarudin, Norhanis Diyana (2014)
Nowadays, most mosques have lost their social characteristics, especially the ones in cities. In other words, it seems that mosques in the present times are operated simply as a house of worship for Muslims, rather than being used as a whole community place. Considering the current situation in Malaysia, it has been stated that the majority of the mosques are only extensively used during the five time congregational prayers and this situation has limited the functions of the mosques outside prayer times. Furthermore, mosque designs nowadays have generated spaces that are more exclusive spaces rather than inclusive. Today, important spaces, such as courtyards, are not incorporated into the mosque designs, and this also affects the declining roles of the open spaces around the mosque. Historically, mosque designs came with courtyards, which played the role of communal spaces for the emergent community during that particular time. However, far too little attention has been paid to the importance and functions of the mosque open spaces as a platform to encourage social and cultural interactions. Hence, the aim of the paper is to provide a conceptual theoretical framework based on ‘how the provision of the mosque open spaces could achieve the intercultural spaces concept and meet the needs of a multicultural society’ and investigating if ‘urban mosque open spaces encourage diverse intercultural activities and interactions’ in Malaysian context. The methodology adopted for this study is a mixed-methods approach, incorporating several techniques, which include systematic observation with behaviour mapping, focus group discussions and interviews. The value of this study lies in investigating whether or not the mosque open spaces in Malaysia encourage communal and intercultural interactions, and, also, in generating new understandings, evidence and knowledge pertaining to the functions and utilisation of the mosque open spaces as communal and intercultural spaces.